Parameter estimation algorithm for a PEM electrolyzer equivalent circuit model under current ripple conditions - Hernández-Gómez, Ángel; Langarica-Cordoba, Diego; Martinez-Rodriguez, Panfilo R.; González-Aguilar, Hernán; Guilbert, Damien; Saldivar, Belem (Electric power systems research, 2026)
Unknown parameter estimation for electrical models of proton exchange membrane (PEM) electrolyzers is important for optimal hydrogen production and storage in power systems. Algorithms for correctly identifying parameters for different models, including equivalent circuit models (ECM), have been reported. These are important for analyzing the transient dynamics of the PEM electrolyzer connected to grid-tied power electronics sources. However, no method has been reported to correctly estimate the ECM parameters when subjected to current ripple from power electronics. Current ripple is an important issue requiring further investigations since they are responsible for the accelerated aging of electrolyzers. In this work, an algorithm has been developed to estimate the parameters of an ECM for the electrolyzer voltage under input current ripple. Furthermore, based on the gradient method, this algorithm allows adapting the parameters with the values of the proposed electronic components, i.e., resistors, capacitors, and voltage sources. The proposed algorithm has been validated using two voltage–current databases obtained from a commercial PEM electrolyzer system NMH2 1000. Thus, by efficiently estimating the ECM parameters, the proposed algorithm facilitates the design and construction of power converters coupled to the electrolyzer under current ripple constraints. •ECM parameter estimation for the voltage of a PEM electrolyzer.•Analysis of the effect of current ripples on PEM electrolyzer.•Development of an algorithm to estimate parameters.•Estimation of activation and concentration voltages based on an equivalent circuit.•Application of the gradient method to the ECM under current ripple conditions.